EFEKTIVITAS PROGRAM KELUARGA HARAPAN DI DESA WADUNGASIH KECAMATAN BUDURAN KABUPATEN SIDOARJO - Reni Allysa Putri Faradina; Lailul Mursyidah (Halu Oleo University, 2025)
The following study aims to describe and evaluate the Effectiveness of the Family Hope Program in Wadungasih Village. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation studies. The informants were selected by purposive sampling, consisting of Beneficiary Families (KPM) and PKH Companions of Wadungasih Village, as those responsible for the Family Hope Program. The informant selection technique used in the following research is purposive sampling, namely technique. The data analysis model used is the Miles Huberman analysis model (1984), which includes data collection, data reduction, data presentation, and conclusion. The results of the study indicate that the effectiveness of the Family Hope program in Wadungasih Village, Buduran District, Sidoarjo Regency has not fully achieved its goals because, in the implementation of the Family Hope Program, the Apparatus is still unable to implement the program properly in understanding the program inaccuracy of targets in receiving PKH assistance. PKH Companions still have several obstacles that prevent them from achieving these goals. This makes the effectiveness of the family hope program in Wadungasih Village still ineffective.